Mangrove litter production in Sei Carang waters of Tanjungpinang City, Riau Island Province - Urai Dian Dharma Putra; Febrianti Lestari; Susiana Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
Sei Carang waters are a mangrove ecosystem area with a fairly wide area coverage, Sei Carang waters have mangrove ecosystems. This study aims to determine the level of mangrove density and production of mangrove litter in Sei Carang. This research was conducted May-June 2022 located in Sei Carang. Observation locations were determined by survey methods and point selection using purposive sampling. Then observations using line transects using a plot measuring 10x10 m. There were 6 species found at the study site, namely: Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorhiza, Bruguiera sexangula, Sonneratia alba, Xylocarpus granatum. The most common types were found at station 1 where there were 6 of them, and at station 3 there were only 4 types. With density levels ranging from 1633.33 ind/ha to 2300 ind/ha. And also the highest litter production value occurs at station 3 with an average value of 7.21 (gbk/m2) and the lowest occurs at station 2 with an average value of 2.27 (gbk/m2), and the parameters of the Sei Carang waters are still relatively low. good for the life of the mangrove ecosystem when compared to seawater Quality Standards Government Regulation of the Republic of Indonesia No. 22 of 2021 concerning the Implementation of Environmental Protection and Management, Attachment VII.